2021
DOI: 10.3390/molecules26164940
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Growth of Large Area Graphene on Si Wafer by a Single Pulse Current

Abstract: Graphene has many excellent optical, electrical and mechanical properties due to its unique two-dimensional structure. High-efficiency preparation of large area graphene film is the key to achieve its industrial applications. In this paper, an ultrafast quenching method was firstly carried out to flow a single pulse current through the surface of a Si wafer with a size of 10 mm × 10 mm for growing fully covered graphene film. The wafer surface was firstly coated with a 5-nm-thick carbon layer and then a 25-nm-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Graphene is grown on the Silicon using Chemical Vapour Deposition (CVD), and another Silicon layer is deposited at the top of graphene material. [45][46][47][48] The device structure is then rotated 90°where the source, drain and channel region are doped with a different concentration using ion implantation with proper masking. After completing the necessary doping of the regions using the ion implantation technique, a very thin film of high κ dielectric material is deposited.…”
Section: Device Architecture and Simulation Set-upmentioning
confidence: 99%
“…Graphene is grown on the Silicon using Chemical Vapour Deposition (CVD), and another Silicon layer is deposited at the top of graphene material. [45][46][47][48] The device structure is then rotated 90°where the source, drain and channel region are doped with a different concentration using ion implantation with proper masking. After completing the necessary doping of the regions using the ion implantation technique, a very thin film of high κ dielectric material is deposited.…”
Section: Device Architecture and Simulation Set-upmentioning
confidence: 99%
“…It is costly to use such a facility for industrial production and is very difficult to scale up. In our previous research work, an ultrafast method was demonstrated for growing large-area graphene on Ni nanotips and Ni-coated Si substrates within 1–2 s by a single pulse current using a simple DC electrical source. , But the sample surface needed to be conductive and connected with two electrodes of an electrical circuit for sample quenching by Joule heat. Up to now, a versatile ultrafast method for graphene film growth remains a challenge.…”
mentioning
confidence: 99%